La Materia e lo Spirito - Michela, Bracardi (Premio Tesi di Dottorato, 2008)
The contribution made by Mario Ridolfi to the construction of a modern Italian identity, in its regional aspect, materialised in his Umbrian designs, starting from the watershed of 1961 which marked the voluntary exile of the architect in Marmore. Through the analysis of his architectural creations, the book reconstructs the mental itinerary pursued by Ridolfi in the elaboration of the Umbrian works, casting light on the architect's interest in the material consistency of the architectural organism, studied in the most minute detail so that the perfection of the work can render it a "living thing". In Ridolfi's work, spirit and matter, art and technology are amalgamated into a single object which always tends to the absolute. Bound up with this, in a play of continual cross-reference, is the study of the specific features of the Umbrian landscape, dominated by the figure of St. Francis of Assisi, as a fruitful and intriguing comparison to map out the contours of the research.